Datenschutz bei drohnengestützter Datenbearbeitung durch Private Dissertation - Henseler, David (sui generis Verlag, 2020)
The usage of drones is constantly increasing, even among private individuals. Anyone who hears or sees a drone usually does not know whether he is being observed or filmed and whether the recorded material is being broadcast live or recorded. It also regularly remains unclear who is responsible for the drone. With this in mind, this book deals with the following question: How can the right to informational self-determination - substantiated in data protection law - be enforced in the case of drone based data processing by private individuals? The author analyses both the future data protection law and the new regulations on drone aviation and presents concrete proposals for an adjustment of the law.